Association between anemia-related biomarkers and the adequacy of peritoneal dialysis in Chinese patients with chronic kidney disease - Li, Jia-Lin; Cai, Zhen; Zhao, Jing; Zhu, Xiang-Gang; Li, Qian; Li, Yan-Shuang; Liu, Meng-Chao; Cui, Fang-Qiang; Zhao, Wen-Jing; Niu, Wen-Quan (Frontiers in Physiology, 2023)
We aimed to examine the association of three anemia-related biomarkers with adequacy of peritoneal dialysis (PD) in patients with chronic kidney disease (CKD).This study included 127 PD patients. Total Kt/Vurea (Kt/V) was calculated according to the K/DOQI guidelines. All patients were classified into two groups based on Kt/V, viz. adequate (Kt/V ≥ 1.7) and inadequate (Kt/V< 1.7) groups. Effect sizes are expressed as odds ratio (OR) and 95% confidence interval (CI).After adjusting for age, gender, hypertension, diabetes and PD duration, per 20 g/L increment in hemoglobin (Hgb) was observed to significantly reduce the risk of inadequate PD by 19% (OR; 95% CI; P: 0.81; 0.70 to 0.95; 0.009), per 5 g/L increment in mean corpuscular hemoglobin concentration (MCHC) by 7% (0.93; 0.88 to 0.98; 0.009), and per 5% increment in transferrin saturation (TS) by 23% (0.77; 0.64 to 0.94; 0.012). Gender-specific nomogram model was constructed by incorporating three significant anemia-related biomarkers, as well as convenient influencing factors, and the prediction accuracy was good (C-index: 0.686 for males and 0.825 for females).Our findings indicate that deterioration of three anemia-related biomarkers (Hgb, MCHC and TS) can precipitate the development of inadequate PD in Chinese patients with CKD.